2002
DOI: 10.1002/chem.200390033
|View full text |Cite
|
Sign up to set email alerts
|

Electron‐Transfer Chemistry of the Iron–Molybdenum Cofactor of Nitrogenase: Delocalized and Localized Reduced States of FeMoco which Allow Binding of Carbon Monoxide to Iron and Molybdenum

Abstract: The electron-transfer chemistry of the isolated iron-molybdenum cofactor of nitrogenase (FeMoco) has been studied by electrochemical and spectroelectrochemical methods. Two interconverting forms of the cofactor arise from a redox-linked ligand isomerism at the terminal iron atom; this is attributed to rotamerism of an anionic N-methyl formamide ligand bound at this site. FeMoco in its EPR-silent oxidised state is shown to undergo three successive one-electron transfer steps. We argue that the first and second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
46
0
2

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 52 publications
5
46
0
2
Order By: Relevance
“…It has been shown that the isolated FeMoco can reduce acetylene ( [63] and references therein) Furthermore, Pickett et al have shown that the isolated FeMo cofactor can be put in an electrochemical system and can be reduced by an applied potential and catalyze the formation of H 2 [64]. It has also been shown that the isolated FeMoco binds CO and shows vibrational frequency shifts similar to those observed in the enzyme [65,66]. However, as in the enzyme, CO does not bind to the FeMoco in the resting state, but only at more reduced states.…”
Section: Enzyme Structurementioning
confidence: 84%
“…It has been shown that the isolated FeMoco can reduce acetylene ( [63] and references therein) Furthermore, Pickett et al have shown that the isolated FeMo cofactor can be put in an electrochemical system and can be reduced by an applied potential and catalyze the formation of H 2 [64]. It has also been shown that the isolated FeMoco binds CO and shows vibrational frequency shifts similar to those observed in the enzyme [65,66]. However, as in the enzyme, CO does not bind to the FeMoco in the resting state, but only at more reduced states.…”
Section: Enzyme Structurementioning
confidence: 84%
“…Recently, the rates and relative intensities of these ν(CO) bands were shown to be sensitive to variation of the side-chain at the α -70 position. [13c] Other CO-related IR bands have been observed during spectro-electrochemical studies of FeMoco (the solvent-extracted version of the FeMo-cofactor), [14] where bands at 1808 and 1835 cm −1 were proposed to arise from bridging CO, whereas features at 1885 and 1920 cm −1 were assigned to terminally bound CO species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it is well known that CO inhibits all substrate reductions in the catalytic process except for H + and spectroscopy has demonstrated that CO can bind to central Fe sites on FeMo-co [31,32] . It has been suggested that several substrates such as N 2 and C 2 H 2 , can interact with the 4Fe4S face of FeMo-co, composed of Fe atoms 2, 3, 6, and 7 (numbered from the X-ray structure) from the work by Igarashi et al [12] and Barney et al 19] .…”
Section: Where Are the Binding And Reduction Site (S) For N 2 And/or mentioning
confidence: 99%